Two outbreak cases involving ST65-KL2 and ST11-KL64 hypervirulent carbapenem-resistant Klebsiella pneumoniae: similarity and diversity analysis - Feilong Zhang; Zhihua Li; Ziyao Li; Xinmeng Liu; Zichen Lei; Xianxia Zhuo; Xinrui Yang; Jiankang Zhao; Yulin Zhang; Binghuai Lu (Communications Biology)
Abstract The rise of the convergence of hypervirulence and carbapenem resistance in Klebsiella pneumoniae has been increasingly reported in recent years, however, there are few outbreak cases for these producing NDM carbapenemase. In this study, ST65-KL2 and ST11-KL64 hypervirulent and carbapenem-resistant K. pneumoniae (hvCRKP) were identified from two different outbreak cases: (1) clonal spreading of ST65-KL2 in five patients within transplantation wards spanning three months; and (2) clonal transmission of ST11-KL64 in ten patients across 10 months. The representative strains of ST65-KL2 and ST11-KL64 hvCRKP, K22877 and K56649, produced carbapenemase NDM-5 and dual carbapenemases KPC-2 and NDM-13, respectively, and both exhibited high-level carbapenem resistance. Moreover, virulent analysis showed that K22877 and K56649 were hypervirulent and the former possessed stronger virulence. Evolutionary pathways suggested ST65-KL2 and ST11-KL64 hvCRKP could be classified as CR-hvKP (hvKP acquiring carbapenem resistance) and hv-CRKP (CRKP acquiring hypervirulence), respectively. Unexpectedly, ST65-KL2 CR-hvKP showed resistance to ciprofloxacin mediated by plasmid acquisition as its spread, and ST11-KL64 hv-CRKP developed into enhanced virulence and macrophage resistance. Furthermore, compared to the ST65-KL2 CR-hvKP, the ST11-KL64 hv-CRKP tends to cause occult and persistent infection. Global genome analysis revealed ST11-KL64 hv-CRKP and ST65-KL2 CR-hvKP mainly carried bla KPC-2 and had significant differences in Ompk35/36, ybt, resistance and virulence. Effective surveillance should be implemented and novel therapeutic strategies are urgently needed to deal with refractory infections.